Penerapan Teknologi Treatment Otomatis Berbasis Fine Bubble Untuk Meningkatkan Hasil Budidaya Nila Cak Na Di Jombang Jawa Timur - Irawan, Dani; Wulandadi, Retno; Marji, Marji; Agustian, Moch. Alfredo Barta; Permadani , Anda (Abdimas Indonesian Journal, 2024)
Cak Na Tilapia Cultivation is a Trading Business Group that focuses on the management and cultivation of tilapia seeds. This group has a tilapia pond of 135 m2 and 72 m2 consisting of 9 plots and 4 fish pond plots. One pond can contain 1000-1500 tilapia seeds. The problems faced by partners are First, the large number of fish that die causes many buyers' orders to decrease because the fish die due to indications of fungus, causing losses due to low productivity. The objectives of this community service are (1) Producing appropriate technology in the form of a Fine Bubble Technology-Based Treatment Machine (2) Providing assistance on how to Automatically Treat fish that are indicated by fungal diseases, (3) Providing technical guidance on maintenance and repair of the filtration system. The method used is by designing technology, training and workshops. The results of community service activities are producing and implementing appropriate technology in the form of a Fine Bubble Technology-Based Treatment Machine in Jombang. This technology has been proven to be able to improve the quality of water in cultivation ponds, such as increasing dissolved oxygen levels and pH stability, which has a positive impact on the growth of Cak Na tilapia.